PENGARUH PEMBERIAN SAFETY TALK TERHADAP KEPATUHAN PENGGUNAAN ALAT PELINDUNG DIRI (APD) PADA PEKERJA BATU BATA - Anggi Isnani Parinduri; Irmayani .; Ismail Sirait (JURNAL KESMAS DAN GIZI (JKG), 2021)
The level of achievement of Occupational Health and Safety (OHS) implementation in brick factories in Indonesia is very low. One of the ways to implement OHS is by conducting safety talk. giving of safety behavior materials is expected to make workers obedient to the use of PPE and increase workers knowledge about PPE. This research was a quantitative study with a quasi-experimental, quasi-experimental approach to the research design using pre-test and post-test. Determination of the number of samples used the purposive sampling method and obtained a sample of 34 workers. The Data collection was carried out by interviewed using a questionnaire and observation sheet. The independent variable in this study was safety talk while the dependent variable is compliance with the use of Personal Protective Equipment (PPE). Evaluation of Compliance with the use of PPE is in the compliance category (55.9%). Statistical tests used the Wilcoxon Signed Rank Test with Î± = 0.05. The results of the analysis showed that there was an effect of providing safety talk on obedience with the use of PPE on brick workers in Sidourip Village, Beringin District in 2020, namely (0.002 â‰¤ 0.05). The conclusion of this study was that there is an influence between safety talk with obedience with the use of PPE. The advice that can be given is that every brick worker must use PPE and attend safety talk activities.